Amino acid transporter SLC38A5 is a tumor promoter and a novel therapeutic target for pancreatic cancer - Tyler Sniegowski; Devaraja Rajasekaran; Souad R. Sennoune; Sukumaran Sunitha; Fang Chen; Mohamed Fokar; Sudhir Kshirsagar; P. Hemachandra Reddy; Ksenija Korac; Mosharaf Mahmud Syed; Tanima Sharker; Vadivel Ganapathy; et al. (Scientific Reports, 2023)
Abstract Pancreatic ductal adenocarcinoma (PDAC) cells have a great demand for nutrients in the form of sugars, amino acids, and lipids. Particularly, amino acids are critical for cancer growth and, as intermediates, connect glucose, lipid and nucleotide metabolism. PDAC cells meet these requirements by upregulating selective amino acid transporters. Here we show that SLC38A5 (SN2/SNAT5), a neutral amino acid transporter is highly upregulated and functional in PDAC cells. Using CRISPR/Cas9-mediated knockout of SLC38A5, we show its tumor promoting role in an in vitro cell line model as well as in a subcutaneous xenograft mouse model. Using metabolomics and RNA sequencing, we show significant reduction in many amino acid substrates of SLC38A5 as well as OXPHOS inactivation in response to SLC38A5 deletion. Experimental validation demonstrates inhibition of mTORC1, glycolysis and mitochondrial respiration in KO cells, suggesting a serious metabolic crisis associated with SLC38A5 deletion. Since many SLC38A5 substrates are activators of mTORC1 as well as TCA cycle intermediates/precursors, we speculate amino acid insufficiency as a possible link between SLC38A5 deletion and inactivation of mTORC1, glycolysis and mitochondrial respiration, and the underlying mechanism for PDAC attenuation. Overall, we show that SLC38A5 promotes PDAC, thereby identifying a novel, hitherto unknown, therapeutic target for PDAC.